Structural and Fiscal Determinants of State Decentralization: A Comparative Legal Study of Poland and Ukraine - Kornieiev, Petro; Brzezicki, Tomasz; Fedchyshyn, Serhii; Kovtun, Maryna; Kovtun, Vitalii (Studia Iuridica Toruniensia, 2026)
The article conducts a comparative legal analysis of decentralization in Poland and Ukraine as a constitutive element of territorial legal personality and a measure of constitutional maturity. Using the dogmatic–legal and systemic methods, it examines constitutional, institutional, and fiscal frameworks through the lens of subsidiarity. The Polish model demonstrates normative stability yet remains constrained by fiscal centralisation and structural disparities, while the Ukrainian model is transitional, marked by legislative dynamism but lacking lasting guarantees of autonomy. Effective decentralization depends on institutional coherence, fiscal equilibrium, and predictable vertical relations. De lege ferenda, the study advocates reinforcing anti-recentralisation mechanisms and fiscal stability in Poland, and full constitutionalization of local self-government in Ukraine in line with subsidiarity, proportionality, and legality.